2012
DOI: 10.1007/978-3-642-30350-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Release Readiness Indicator for Mature Agile and Lean Software Development Projects

Abstract: Abstract. Large companies like Ericsson increasingly often adopt the principles of Agile and Lean software development and develop large software products in iterative manner -in order to quickly respond to customer needs. In this paper we present the main indicator which is sufficient for a mature software development organization in order to predict the time in weeks to release the product. In our research project we collaborated closely with a large Agile+Lean software development project at Ericsson in Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…[50,47]), a release management workflow [47] or a continuous delivery workflow [46,47] appear also in the literature as enablers of CD. Staron et al [74] present a release readiness indicator, a mechanism to predict in which week the release would be possible given the defect history. In addition, some studies discuss fast release in the context of ASD.…”
Section: Mechanisms For Achieving Fast and Frequent Releasementioning
confidence: 99%
See 1 more Smart Citation
“…[50,47]), a release management workflow [47] or a continuous delivery workflow [46,47] appear also in the literature as enablers of CD. Staron et al [74] present a release readiness indicator, a mechanism to predict in which week the release would be possible given the defect history. In addition, some studies discuss fast release in the context of ASD.…”
Section: Mechanisms For Achieving Fast and Frequent Releasementioning
confidence: 99%
“…Empirical evidence shows that most companies typically perform testing activities late in the development process causing unpredictable additional development efforts [60] and significant delays in releases [74]. Many primary studies emphasise the importance of employing testing and quality assurance (QA) practices throughout the whole development process in the context of CD, as features are rolled out, and not just at the end of the development (e.g.…”
Section: Continuous Testing and Quality Assurancementioning
confidence: 99%
“…The release readiness prediction, which is an indicator combining measures of the number of defects reports open, number of tests to execute, and a function of test progress. More details on the definition can be found in the work of Staron and Meding Product downtime in field, which is a measure collected from the product log files reported by the customers on regular intervals, combines the measures of time in use and downtime of a product and aggregates that per product line.…”
Section: Measurement Systemsmentioning
confidence: 99%
“…Baccelli and Bird [14] investigated the outcomes and challenges of modern tool-based code reviews and observed that, amongst other things, code reviews are not only used for revealing defects, but also serve to promote awareness and knowledge transfer. Slightly related to velocity is the work of Staron et al [15]. They identified the time-to-release as the main indicator for release readiness based on a number of metrics.…”
Section: Related Workmentioning
confidence: 99%